(untitled) (International Journal of Engineering and Computer Science, 2015)
This interacting device is a large scale microcontroller based system being designed to facilitate the communication among the deaf and dumb communities and their communication with the normal people. This system can be dynamically reconfigured to work as a “smart device”. In this paper, Atmega 328 and sensors based interacting device is presented. The device discussed is basically a data glove and a microcontroller based system. Data glove can detect almost all the movements of a hand and microcontroller based system converts some specified movements into human recognizable voice. The data glove is equipped with two types of sensors: The bend sensors and accelerometers as tilt sensors. This system is beneficial for dumb people and their hands will speak having worn the interacting device data glove.